Ethische Analyse lebensverlängernder Behandlungen: zum Schutz der Selbstbestimmung und zum Schutz vor Übertherapie = Ethical analysis of life-prolonging treatment : for protection of self-determination and protection against overtreatment - Mehlis, Katja; Winkler, Eva C. (Der Onkologe, 2016)
BackgroundDue to improved treatment options the importance of reasoned decisions against life-prolonging treatment is increasing. Especially in patients with advanced cancer such decisions are necessary to prevent overtreatment at the end of life. They are, however, often accompanied by clinical, communicative and ethical challenges for the patients and the medical team.ObjectivesIn this article the reasons behind the justification and limitation of life-prolonging treatment in the case of persons with and without a decision-making capability are explained from a medical ethics perspective. In particular, evidence is provided for the relevance of advanced care planning and shared decision-making together with the patient. Concrete suggestions for solutions to improve the clinical situation are presented in order to get to know patient preferences and to meet them in an ethically responsible way.Material and methodsBased on the available literature and own data we present the medico-ethical considerations with respect to the limitation of life-prolonging treatment.Results and conclusionStudies have shown that early discussions with the patient on planning of the end of life improve patient quality of life and allow them to develop a more realistic understanding of the situation. Knowing the patient’s preferences is also a prerequisite for shared decision-making on the intensity of treatment near to death. While there are clear guidelines to identify the will of patients with no decision-making capability, comparable standards for persons who are still able to give consent are missing. Currently, decisions against life-prolonging treatment are often communicated too late or not at all with the patient in advance.